2021
DOI: 10.3389/fphar.2021.761551
|View full text |Cite
|
Sign up to set email alerts
|

HPLC-DAD Fingerprints Combined With Multivariate Analysis of Epimedii Folium From Major Producing Areas in Eastern Asia: Effect of Geographical Origin and Species

Abstract: The growth location and plant variety may influence the active components and biological activities of plants used in phytomedicine. In this study, nine sets of different Epimedii Folium, from different representative cultivation locations and Epimedium species, were collected for comparison, using HPLC-DAD combined with multivariate analysis. The objective was to investigate the influence of geographical origin and Epimedium species on the quality of Epimedii Folium, and provide applicable guidance for cultiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The time window width was set to 0.1 min, and the median method was selected for full-spectrum peak matching. The simulated average fingerprint R was generated, the similarity between the sample and the average fingerprint R was calculated, and then the common peaks that existed in each herb were observed [21]. A chemometric analysis including HCA and PCA was used to examine the similarities and differences between the samples [22].…”
Section: Statistical Analysis Of the Hplc Fingerprintsmentioning
confidence: 99%
See 1 more Smart Citation
“…The time window width was set to 0.1 min, and the median method was selected for full-spectrum peak matching. The simulated average fingerprint R was generated, the similarity between the sample and the average fingerprint R was calculated, and then the common peaks that existed in each herb were observed [21]. A chemometric analysis including HCA and PCA was used to examine the similarities and differences between the samples [22].…”
Section: Statistical Analysis Of the Hplc Fingerprintsmentioning
confidence: 99%
“…As the raw material of a standard decoction, the quality of the TCM herbs is affected by origin, harvesting season, storage time, processing method, etc., which largely determines the efficacy of TCM preparations. The TCM fingerprint is a comprehensive, quantifiable technology that can provide more detailed information regarding the type and contents of the TCM components [20,21]. As data mining methods have developed, chemometrics has gained more and more attention because it can simplify complex data and uncover hidden patterns.…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, the crude drugs listed in the Japanese Pharmacopeia and EH extracts are usually included in energy drinks for tonicity. Its main ingredients are prenylated flavonoids (Ma et al, 2011;Li et al, 2021), especially icariin (Figure 1), which suppresses nerve degeneration, improves cognitive function in neurological disorders (Guo et al, 2010), and has neuroprotective effects (Li et al, 2022). It has also been suggested that icariin inhibits AGE-derived neuropathy in PC12 cells (Zhao et al, 2019); RAGE might be a potential target for Epimedium's antineuroinflammatory role in vascular dementia, which is an insight from network pharmacology and molecular simulation (Yuan et al, 2023), and extracts including icariin may reduce the risk of atherosclerosis by inhibiting the formation of AGEs on HDL (Kim and Shim, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…To date, over 300 compounds have been identified within the Epimedium genus, including four specific compounds: epimedin A, B, C and icariin ( Ren et al., 2018 ), which serve as bioactive markers for Epimedium ’s quality control ( Xie et al., 2010 ; Ma et al., 2011 ). China has abundant wild resources of Epimedium , with considerable variation in the levels of these four compounds, impacting the raw material’s final quality ( Li et al., 2021 ). Although several studies have been reported the accumulation of these main compounds in Epimedium , there are still lacking reports for some populations of wild Epimedium , such the ESMs.…”
Section: Introductionmentioning
confidence: 99%